Comparison of corrosion of magnesium and aluminium in palm biodiesel / Chew King Vee - Chew, King Vee (2013)
Salat is an Islamic prayer ritual that all Muslims must perform five times a day. The salatphysical manoeuvres steps include various motions such as standing, bowing, prostration, and sitting. Recently, the study of salat movements from the perspective of science has been widely investigated. The current study evaluated the impact of salatmovements on the biomechanical response of human muscle using electromyography (EMG). The eight upper-bodymuscles involved were the neck extensors (NE), sternocleidomastoideus (SCM), trapezius (TRP), deltoid (DL), bicepsbrachii (BB), triceps brachii (TB), rectus abdominus (RA), and erector spine (ES) and the four lower-body muscles involved were the rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA), and gastrocnemius (GAS) muscles. A group of undergraduates aged between 19 to 28 years voluntarily participated in this study. The subjects were asked to performsalat movements(takbir, bowing, prostration, sitting, and salam) and specified exercises (squat exercise and toe touching exercise). During the experiment, the root mean square (RMS) and maximum voluntary contraction (MVC) for each muscle in every position of salatwas recorded. The result showed that the muscles produced different EMG levels during each salat’s positions. For example, the highest EMG level achieved during the ‘takbir’movement was at the TRP (23.11% MVC), followed by DL (10.57%MVC), BB (9.75%MVC), ES (5.50%MVC), NE (3.93%MVC), RA (3.25%MVC), SCM (2.94%MVC), and TB (2.61%MVC). Forstatisticalanalysis, the Wilcoxon’sRank Sum Test was used to compare the neighbouring and antagonistic muscles: NE to SCM, TRP to DL, BB to TB, and ES to RA. The finding showed that there were significant differences in the performances for all the antagonist muscles during each salat’sposition (p<0.05). For the comparison between the salat and the specified exercises, the test found a statistically no significant difference between salatand the specified exercises for the RF, BF, and GAS, but for the TA, there was significant difference with a difference of 5.67%MVC. Muscle contraction and relaxation that occurred showed an agonist-antagonist response which is good for exercise and strengthening programmes. Hence, the current experiment can be taken as a pilot study on the biomechanical response of the human muscles during the act of performing the salat.